PENGARUH PENGGUNAAN NR DAN NBR DENGAN BAHAN PENGISI SILIKA TERHADAP SIFAT FISIKA KOMPON ROL KARET CPO - Prasetya, Hari Adi (Balai Riset dan Standardisasi Industri Palembang, 2010)
The research aimed to obtain the influence of natural rubber NR, synthetic rubber NBR and alumunium silikat (AISiOâ) as a filler, its physical properties and also to find out rubber compound the best for rubber mixture with variation of NR : NBR 50, 70 : 30, 90 : 10 hr and variation of aluminium silikat (ASiOâ) 45 phr, 50 phr, 55 phr. The result showed that the addition of rubber NR : NBR ratio and alumunium silikat (ASiOâ) had significant effect on the hardness, tensile strength, abration recistance and compression set. The addition of rubber NR : NBR ratio and alumunium silikat (ASiOâ) gave significant effect on the density of the rubber roll CPO compound. The best treatment was found to be the NâPâ (the addition of rubber NR : NBR = 70 : 30 phr and alumunium silikat 50 phr) with the rubber roll CPO compoundâs characteristics of 78 shore A for hardness, 228 kg/cm2 Â for the tensile strength, 87,6 kg/cm2 for the abration recistance and 22,60% for the compression set.